2021
DOI: 10.3390/ijerph18137198
|View full text |Cite
|
Sign up to set email alerts
|

Disasters, Gender, and HIV Infection: The Impact of the 2010 Haiti Earthquake

Abstract: Although disasters threaten all people who experience them, they do not affect all members of society in the same way. Its effects are not solely restricted to the economic sphere; they also affect the physical and mental health of those who suffer from them, having a particular impact on women and limiting their life chances. The aim of this study was to examine the impact the 2010 Haiti earthquake had on the seropositivity of female survivors. Method: Using data from the Demographic and Health Survey, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Some studies investigate the possible impact of specific natural disasters on mental health. Llorente-Marrón et al [ 35 ] found that earthquakes have a negative impact on the physical and mental health of victims. The study by Gissurardóttir et al [ 36 ] suggested that exposure to volcanic eruptions may lead to mental health disorders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies investigate the possible impact of specific natural disasters on mental health. Llorente-Marrón et al [ 35 ] found that earthquakes have a negative impact on the physical and mental health of victims. The study by Gissurardóttir et al [ 36 ] suggested that exposure to volcanic eruptions may lead to mental health disorders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2,6 Additionally, other types of public health crises, such as natural disasters including floods, droughts, or earthquakes, have also been documented to impose major challenges on PLWH due to impacts on physical infrastructure. [7][8][9] For example, in March 2020, Kenya's rainy season intensified unexpectedly through May 2020. Over 233,000 individuals across 75% of the country's counties (primarily in western Kenya) were impacted leading to health emergencies, displacement, flash floods, landslides, and death.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to achieve real benefits for science and society, an effective approach should not limit to analyzing a variable only, i.e., gender, but instead should include more sociodemographic factors, overlapping or intersecting categories, such as gender, ethnicity, age, socio-economic status (Tannenbaum et al, 2019), being the approach referred as intersectional 4 . Obviously, this does not mean an 'add and stir' approach, but rather requires a full shift in mindset (UNWomen, 2022), with significant achievements (e.g., Llorente-Marrón et al, 2021;Hall et al, 2022;Luna and Hilhorst, 2022).…”
mentioning
confidence: 99%